Correlative morphological and biochemical changes during in vitro capacitation of spermatozoa in Cross bred bulls - DHANJU, C K; CHEEMA, RANJNA S; KAUR, RAVINDER (The Indian Journal of Animal Reproduction, 2023)
The pattern of motility of spermatozoa at an interval of 2hr, percentage of acrosome reaction (AR) and changes in biochemical constituents of spermatozoa and their membrane extracts (SME) i.e. proteins, lipids, phospholipids and cholesterol and their leakage in incubation medium (IM) were studied during in vitro capacitation of spermatozoa in freshly ejaculated semen of cross bred bulls after incubation in TALP medium at 37°C for 6hr. Initial motility of spermatozoa was 76 to 80% which declined by l5 to 21% after 6hr incubation in TALP medium as compared to 55 to 62% under control conditions. The motility of spermatozoa was mostly forward and they started showing darting and zigzag movements after 3-4 hr of incubation which confirmed the occurrence of capacitation. vesiculation and acrosome shedding of spermatozoa was observed and their number counted in stained smears of spermatozoa and expressed as percentage of capacitation and AR which was found to be 62- 87%. Statistically significant (p<0.05) decrease in proteins, lipids, phospholipids and cholesterol contents of spermatozoa was observed during capacitation and these biochemical changes revealed that a remodeling of the sperm membrane occurs during capacitation which prepares it for the exocytotic event of the acrosome reaction.